1967
DOI: 10.1017/s0022029900012401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxidation on the iodine values of phospholid in milk, butter and washed-cream serum

Abstract: SummaryPhospholipid was isolated from milk, butter, and washed-cream serum by solvent extraction followed by simple counter-current distribution and thin-layer chromatography. Iodine values from fresh samples, determined by a micro-Wijs technique, ranged, for the cephalin fraction, from 70 to 86, for the lecithin fraction from 44 to 55, and for the sphingomyelin fraction from 36 to 44. In washed-cream serum, oxidation with copper and ascorbic acid led to reduction in extractable phosphorus, decreased chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The decreased mobility of SPC-B on thin layers may therefore be due to oxidation known to affect the chromatographic behavior of phospholipids. May and McCay (1968), Sessa et al (1974), and also Pont and Holloway (1967) reported decreases in the mobility of oxidized phospholipids on TLC. According to Pont and Holloway, the mobility of both oxidized phos-phatidylcholine and phosphatidylethanolamine compared to the Rf value of sphingomyelin in chloroform-methanol-water (65:25:4).…”
Section: Resultsmentioning
confidence: 95%
“…The decreased mobility of SPC-B on thin layers may therefore be due to oxidation known to affect the chromatographic behavior of phospholipids. May and McCay (1968), Sessa et al (1974), and also Pont and Holloway (1967) reported decreases in the mobility of oxidized phospholipids on TLC. According to Pont and Holloway, the mobility of both oxidized phos-phatidylcholine and phosphatidylethanolamine compared to the Rf value of sphingomyelin in chloroform-methanol-water (65:25:4).…”
Section: Resultsmentioning
confidence: 95%